1999
DOI: 10.1053/ejvs.1998.0723
|View full text |Cite
|
Sign up to set email alerts
|

A Policy of Quality Control Assessment Helps to Reduce the Risk of Intraoperative Stroke During Carotid Endarterectomy

Abstract: Our policy of TCD plus angioscopy has continued to contribute towards a sustained reduction in the risk of IOS following CEA, but requires access to reliable equipment and technical support. However, a policy of intraoperative quality control assessment may not necessarily alter the rate of postoperative stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…12 Our data have suggested that approximately 50% of patients will have Ն1 emboli detected during the 3-hour period of postoperative TCD monitoring. 13 Of these, Ͻ5% will undergo high-grade embolization, 4 defined as Ն25 emboli in a given 10-minute period. 9 It has been shown independently and conclusively by 5 different research centers worldwide that in the postoperative period, increasing rates of embolization are seen before manifestation of a neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Our data have suggested that approximately 50% of patients will have Ն1 emboli detected during the 3-hour period of postoperative TCD monitoring. 13 Of these, Ͻ5% will undergo high-grade embolization, 4 defined as Ն25 emboli in a given 10-minute period. 9 It has been shown independently and conclusively by 5 different research centers worldwide that in the postoperative period, increasing rates of embolization are seen before manifestation of a neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative stroke, apparent on recovery from anesthesia, was reduced in the last 1200 patients from 4% to 0.25% by introducing a policy of intraoperative transcranial Doppler (TCD) monitoring and completion angioscopy. 3,4 However, this failed to prevent postoperative stroke due to thrombosis of the endarterectomy zone, which continued to complicate 2.7% of CEAs. 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40,57,58 Microembolic signals most commonly occur during the dissection phase intraoperatively, during shunting and unclamping, during wound closure, and in the first few hours postoperatively. [59][60][61][62][63][64][65][66] The number of microembolic signals during dissection correlates best with new ischemic lesions seen on MRI 62 and postoperative cognitive deterioration. 59 The presence of Ͼ50 microembolic signals/hour during the early postoperative phase is reported to predict the development of ipsilateral focal cerebral ischemia.…”
mentioning
confidence: 96%
“…1 Postoperative carotid thrombosis is preceded by increasing embolization, which can be detected by transcranial Doppler, and there is increasingly convincing evidence that the postoperative transcranial Doppler signals represent platelet microemboli. 2 We have previously shown that the rate of postoperative embolization is related to the inherent responsiveness of the patients' platelets to adenosine diphosphate (ADP).…”
mentioning
confidence: 99%